2020
DOI: 10.3389/fmicb.2020.573586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus fermentum CQPC04 on Lipid Reduction in C57BL/6J Mice

Abstract: Probiotics are functional foods that can effectively regulate lipid reduction and maintain body health. In this study, a strain of Lactobacillus fermentum CQPC04 (LF-CQPC04) isolated from traditional naturally fermented vegetables (Sichuan pickles) was studied, and its effects on lipid reduction in mice, as well as its mechanism of action, were observed. The results of this experiment show that LF-CQPC04 can reduce the abnormal weight gain and abnormal visceral index of mice caused by a high-fat diet. LF-CQPC0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, we found the Angptl4 and LPL expression were both increased, which might be related to the SCFAs generated in colon, just as a report from Jiao et al ( 45 ) that SCFAs could reduce lipogenesis, and enhance lipolysis in different tissues of pigs via regulating related hormones and genes. CPT1 is a rate-limiting enzyme in the β-oxidation process of fatty acids and located in the outer mitochondrial membrane, catalyzing the transfer of long-chain fatty acids from acyl-CoA to carnitine, then it enters the mitochondria from the cytoplasm for oxidation ( 14 ). The upregulated hepatic CPT-1 mRNA expression demonstrated that fatty acid β-oxidation might be enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found the Angptl4 and LPL expression were both increased, which might be related to the SCFAs generated in colon, just as a report from Jiao et al ( 45 ) that SCFAs could reduce lipogenesis, and enhance lipolysis in different tissues of pigs via regulating related hormones and genes. CPT1 is a rate-limiting enzyme in the β-oxidation process of fatty acids and located in the outer mitochondrial membrane, catalyzing the transfer of long-chain fatty acids from acyl-CoA to carnitine, then it enters the mitochondria from the cytoplasm for oxidation ( 14 ). The upregulated hepatic CPT-1 mRNA expression demonstrated that fatty acid β-oxidation might be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, metabolites of gut microbes, such as short chain fatty acids (SCFAs) not only is of importance in gut health as signaling molecules, but also might enter the systemic circulation and directly affect the metabolism or function of peripheral tissues ( 13 ). SCFAs is considered as a bridge linking gut microbiota and parenteral tissues ( 13 ), which exhibit a vital role in fat accumulation via affecting lipid metabolism, energy metabolism and appetite ( 14 ). In recent years, an increasing attention are paid on intervention studies of probiotics influencing lipid metabolism via manipulation of gut microbiota and metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusion drawn by Wa et al (2019) through their findings suggested that the lipid-metabolism-related gene modulation of single probiotics was more efficacious in comparison to the combined probiotics (Wa et al, 2019). Yi et al (2020) evaluated the lipid reduction effects and mechanism of action of L. fermentum CQPC04, isolated from traditional naturally fermented vegetable, Sichuan pickle. In this in-vivo study conducted in 6-week-old C57BL/6J mice, the Lactobacillus fermentum CQPC04 showed reduction in abnormal weight gain and abnormal visceral index of mice caused by a high-fat diet.…”
Section: Habitats Of Lactobacillusmentioning
confidence: 99%
“…Since abnormal levels of ALT, AST, AKP are markers of liver damage, their reduction in this finding suggested that Lactobacillusfermentum CQPC04 could prevent liver damage and as a result prevent obesity and obesity-related disorders. Further, this Lactobacillus strain could also decrease the levels of inflammatory cytokines, like IL-6 (interleukin-6), IL-1β (interleukin-1 beta), TNF-α (tumor necrosis factor alpha), and IFN-γ (interferon gamma) in the serum of high-fat mice (Yi et al, 2020). Mu et al (2020) studied the in-vivo lipid-reducing property of L. plantarum KFY02 isolated from naturally fermented yogurt on C57BL/6J mice.…”
Section: Habitats Of Lactobacillusmentioning
confidence: 99%
See 1 more Smart Citation